Kato inequality for operators with infinitely many separated variables - Samoilenko, V. G. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
We find conditions under which the Kato inequality is preserved in the case where, instead of an operator with finitely many variables, an operator with infinitely many separated variables is taken. We use the inequality obtained to study both self-adjointness of the perturbed operator with infinitely many separated variables and the domain of definition of the form-sum of this operator and a singular potential.